Revisiting the Scientific Foundations of Forensic Science - A. V. Nesterov (Теория и практика судебной экспертизы, 2018)
The study addresses recent criticisms of forensic science, specifically those pointing to a lack of sound scientific basis behind examination methods. Conclusions are based on the analysis of documents published in the United States, as well as forensic expert practices in Russia. Analysis demonstrates both methodological and legal issues with the application of specialized knowledge in the expert form. The use of Karl Popper’s principle to support the scientific status of forensic methods is demonstrated to lack justification, and is therefore debatable.